John Fowls's Mystery: a Problem of Continuity - Melnikova, Irina (Respectus Philologicus, 2002)
The paper deals with the problem of continuity in postmodernist text. In order to explicate some aspects of the problem and to present a possible solution, the author applies the intertextual approach and tries to analyse one of short stories from The Ebony Tower by John Fowles, which pivots on disappearance of MP John Marcus Fielding. The surface structure of The Enigma gives an opportunity to interpret it as the formal detective fiction (the main elements of it – crime, detective, investigation and solution), which does not follow the formulaic rules because of non-formulaic ending. And what is more, two fragments of the text form two unconnected different spaces one of them being surplus to another.In their attempts to explain the reasons of surprising turn of events at the end of the story, as well as to solve the problem of distinguishing between the structuring forces of the romantic quest and those of detection, critics tried to make a structural analysis of the detective elements in The Enigma. Such kind of investigation (an attempt to show formal architextual relationship) allowed interpreting the particular device (the turn of events at the end of the story) as a shift from one genre to another – from formal detective fiction to romance. So far as critics observe external architextual dialogue with detective fiction, they suggest mechanic combination of fragments in the text and are unable to solve the problem of meaningful continuity.In contrast to the method mentioned above, the intertextual approach presented in the paper seems to be able to propose a solution.The identification of intertextual quotations reveals the architextual relations of another kind (the dialogue between The Enigma and the novel of the Age of Enlightenment, which offers a deeper understanding of the story's form) and proposes the semantic bases of continuity – the system of ethic and aesthetic values of Taoism. Taoist image of the world, the functions of word in Taoism help to understand the strange 'open' end of the story and to reconstruct its continuity (i.e. to understand the text as the meaningful continuum – a unit of significance).
Keywords: continuity; architextuality; intertextuality; semiotic analysis; motive; meaning; significance; detective story; Taoism